Ethnobotanical Uses, Phytochemical Insights, and Therapeutic Potential of Calotropis Species in Nepal - Panta, Kalyan (AWADHARANA, 2025)
Calotropis procera and Calotropis gigantea are prominent medicinal plants distributed across the lowlands (below 1000 m elevation) in Nepal and wider in South Asia. They hold long-standing ethnomedicinal value, particularly in the treatment of skin infections, digestive disorders, respiratory conditions, pain, and wound healing. This review synthesizes published ethnobotanical records, phytochemical studies, and traditional knowledge to provide an overview of their medicinal importance in Nepal. Reported bioactive compounds, including glycosides, flavonoids, alkaloids, phenolics, and terpenoids, are associated with anti-inflammatory, antimicrobial, analgesic, and regenerative properties. The latex, while therapeutically significant, also contains toxic principles that necessitate caution and standardized dosage. Overall, the evidence highlights both the therapeutic promise and the potential risks of Calotropis species, underscoring the need for further pharmacological validation and safety-focused research in the Nepalese context.